Linking early diagenesis and sedimentary facies to sequence stratigraphy on a prograding oolitic wedge: The Bathonian of western France (Aquitaine Basin). (March 2017) - Andrieu, Simon; Brigaud, Benjamin; Barbarand, Jocelyn; Lasseur, Eric
Abstract: To improve the understanding of the distribution of reservoir properties along carbonate platform margins, the connection between facies, sequence stratigraphy, and early diagenesis of discontinuities along the Bathonian prograding oolitic wedge of the northeastern Aquitaine platform was investigated. Eight facies are distributed along a 50 km-outcropping transect in (1) toe-of-slope, (2) infralittoral prograding oolitic wedge, (3) platform margin (shoal), (4) open marine platform interior, (5) foreshore, and (6) terrestrial settings. The transition from shallow platform to toe-of-slope facies is marked in the field by clinoforms hundred of meters long. Carbonate production was confined to the shallow platform but carbonates were exported basinward toward the breakpoint where they cascaded down a 20–25° slope. Ooid to intraclast grainstones to rudstones pass into alternating marl-limestone deposits at an estimated paleodepth of 40–75 m. Three sea-level falls of about 10 m caused the formation of discontinuities corresponding to sequence boundaries. Along these discontinuities, erosional marine hardgrounds formed in a high-hydrodynamic environment at a water depth of less than 10 m, displaying isopachous fibrous cements and meniscus-type cements. The cements pass landward into meniscus and microstalactitic forms along the same discontinuities, which are characteristic of subaerial exposure. During the deposition of transgressive systems tracts, carbonate accumulation remained located mostly on the shallow platform. Energy level increased and carbonates were exported during the deposition of highstand systems tracts forming the infralittoral prograding oolitic wedge. During the deposition of lowstand systems tracts, carbonate production fell to near zero and intraclast strata, derived from the erosion of hardgrounds on the shallow platform, prograded basinward. Early diagenetic cements are related exclusively to discontinuities that are not found within the prograding wedge because of the continuous high sedimentation rate under lower hydrodynamic conditions. This absence of early cementation within the infralittoral prograding oolitic wedge was conducive to porosity conservation, making such features good targets for carbonate reservoir exploration. This study proposes a novel sequence stratigraphy model for oolitic platform wedges, including facies and early diagenesis features. Graphical abstract: Highlights: A novel sequence stratigraphy model for oolitic carbonate platform wedges. Clinobeds are about 120 m long and their base is located at a depth of 40–75 m. During LSTs the erosion of hardgrounds results in intraclast deposit downslope. Early cements are absent from the infralittoral prograding oolitic wedge.